Dynamic Equilibrium and the Real Exchange Rate in a Spatially Separated World - Dumas, Bernard (Review of Financial Studies, 1992)
Two homogeneous stocks of physical capital are located in two different countries, separated by an "ocean." They are consumed by local residents, invested in a random production process yielding real returns, or transferred abroad. Under proportional transfer costs, trade, consumption, and capital imbalances are shown to be persistent. The heteroskedastic process for the relative price of capital in the two countries has a nonlinear, mean-reverting drift. Nevertheless, the conditional probability of the price moving from the parity value of unity is greater than the probability of it moving toward parity. The real interest-rate differential incorporates a simple risk premium. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.